Net water uptake within the ischemic penumbra predicts the presence of the midline shift in patients with acute ischemic stroke - Chen, Cuiping; Yang, Jianhong; Han, Qing; Wu, Yuefei; Li, Jichuan; Xu, Tianqi; Sun, Jie; Gao, Xiang; Huang, Yi; Parsons, Mark W.; Lin, Longting (Frontiers in Neurology, 2023)
Objective The study aimed to explore the association between midline shift (MLS) and net water uptake (NWU) within the ischemic penumbra in acute ischemic stroke patients. Methods This was a retrospective cohort study that examined patients with anterior circulation stroke. Net water uptake within the acute ischemic core and penumbra was calculated using data from admission multimodal CT scans. The primary outcome was severe cerebral edema measured by the presence of MLS on 24 to 48 h follow-up CT scans. The presence of a significant MLS was defined by a deviation of the septum pellucidum from the midline on follow-up CT scans of at least 3 mm or greater due to the mass effect of ischemic edema. The net water uptake was compared between patients with and without MLS, followed by logistic regression analyses and receiver operating characteristics (ROCs) to assess the predictive power of net water uptake in MLS. Results A total of 133 patients were analyzed: 50 patients (37.6%) with MLS and 83 patients (62.4%) without. Compared to patients without MLS, patients with MLS had higher net water uptake within the core [6.8 (3.2–10.4) vs. 4.9 (2.2–8.1), P = 0.048] and higher net water uptake within the ischemic penumbra [2.9 (1.8–4.3) vs. 0.2 (−2.5–2.7), P < 0.001]. Penumbral net water uptake had higher predictive performance than net water uptake of the core in MLS [area under the curve: 0.708 vs. 0.603, p < 0.001]. Moreover, the penumbral net water uptake predicted MLS in the multivariate regression model, adjusting for age, sex, admission National Institutes of Health Stroke Scale (NIHSS), diabetes mellitus, atrial fibrillation, ischemic core volume, and poor collateral vessel status (OR = 1.165; 95% CI = 1.002–1.356; P = 0.047). No significant prediction was found for the net water uptake of the core in the multivariate regression model. Conclusion Net water uptake measured acutely within the ischemic penumbra could predict severe cerebral edema at 24–48 h.